1982
DOI: 10.1111/j.1399-3011.1982.tb03069.x
|View full text |Cite
|
Sign up to set email alerts
|

Solution conformations of oligomers of α ‐aminoisobutyric acid°

Abstract: The N‐acetyl(Aib)nN' ‐methylamides (with n= 1, 2 and 3) and the N‐acetyl‐(Aib)3 methyl ester have been synthesized using an oxazolone procedure. An experimental conformational analysis of this series of oligomers has been carried out in water, DMSO‐d6 and CDCI3 using n.m.r. techniques, and in chloroform using i.r. spectroscopy. Deuterium exchange rates of amide protons in DMSO‐d6 and the rates of change of these proton chemical shifts with temperature in water, DMSO‐d6 and CDCI3 indicate that the oligomeric N'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…5). A similar NH frequency value was previously indicated for a C5 conformer in derivatives of 2-aminoisobutyric acid [19][20][21] and diethylglycine. 27 The present observations for 1-3, aided by further insights from theoretical gas phase studies (ESI Section S2.5 †), suggest that this is the characteristic signature of a C5 interaction in a,a-disubstituted amino acid derivatives in solution.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…5). A similar NH frequency value was previously indicated for a C5 conformer in derivatives of 2-aminoisobutyric acid [19][20][21] and diethylglycine. 27 The present observations for 1-3, aided by further insights from theoretical gas phase studies (ESI Section S2.5 †), suggest that this is the characteristic signature of a C5 interaction in a,a-disubstituted amino acid derivatives in solution.…”
Section: Resultssupporting
confidence: 86%
“…In this area, one of the most enigmatic phenomena is the intra-residue interaction between the N-H and C]O dipoles known as the C5 H-bond. 14 Pioneering studies [15][16][17][18][19][20][21] and salutary subsequent work [22][23][24] on model compounds suggested that this weak interaction succumbs easily to C7 or C10 H-bonds which stabilize folded structures in solution (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…For (Aib) n homo‐peptides in helix‐supporting solvents (e.g. CDCl 3 ), the same conformation (3 10 ‐helix) is largely prevailing . Using Fourier transform infrared spectroscopy (FTIR) absorption and 1 H NMR, we established that populations close to 90% and 100% of 3 10 ‐helical conformers are attained at the hexamer and octamer level, respectively.…”
Section: Cα‐tetrasubstituted α‐Amino Acidsmentioning
confidence: 95%
“…Synthesis of the molecules was carried out at Fairfield University. The most direct synthesis of the three peptide samples was to couple the oxazolone of Ac-Aib–Aib-OH to the three different amine caps in dry MeCN (overnight reflux). , After isolation, the peptides were purified using flash silica gel chromatography. Crystals for X-ray analysis were grown via diffusion of diethyl ether into a solution of methylene chloride.…”
Section: Methodsmentioning
confidence: 99%